Susceptibility of foodborne Pathogens and Spoilage Microorganisms to seed extracts of Citrullus Vulgaris and Citrus Reticulata (Journal of Bio-Science, 2015)
Context: The importance of herbs in the management of food borne pathogens and spoilage organisms is of current interest since many plant components are bioactive and relatively safe when taken. Plant parts of Citrus reticulata and Citrullus vulgaris are used in herbal therapy in some parts of the world. Objective: The objective of this study was to evaluate the susceptibility of foodborne pathogens and spoilage microorganisms to seed extracts of Citrus reticulata and Citrullus vulgaris. Materials and Methods: The antimicrobial effect of ethanol and hot water extracts of C reticulata and C vulgaris seeds were studied using agar well diffusion technique. Minimum inhibitory concentration was performed using the modified tube dilution technique. The extracts were assayed on pure cultures of Bacillus subtilis, Staphylococcus aureus, Salmonella typhi, Escherichia coli, Saccharomyces cerevisiae and Aspergillus flavus. Results: Extracts tested at various concentrations produced in-vitro antimicrobial activities against foodborne isolates of B subtilis, S aureus, S typhi, E coli, S cerevisiae and A flavus. The highest zone of inhibition was obtained from ethanol extract at 4000?g/ml against B subtilis with diameter of 25mm for C reticulata. The lowest zone of inhibition of 10mm was obtained for E coli at 4000g/ml for the hot water extract of C vulgaris. The minimum inhibitory concentration (MIC) of the water extract of C reticulata and C vulgaris seeds ranged between 125-2000?g/ml. The MIC of the ethanol extract of the seeds of both plants was in the range 62.5-1000?g/ml.Comparatively, the ethanol extract of the seeds were more potent than the hot aqueous extract. The percent killing of the ethanol extract at 2000?g/ml was higher for C reticulata (45.6-100%) compared to that of C vulgaris (35.6-87.5). Conclusion: The results show that the ethanol extracts of Citrus reticulata and Citrullus vulgaris have potentential application for shelf life extension and as a pharmaceutical preparation. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22520 J. bio-sci. 21: 61-68, 2013